2022
DOI: 10.1108/jeas-05-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

Humanoid psychological sentiments and enigma of investment

Abstract: PurposeThe primary goal of this study is to look at the behavioral factors that influence an individual's decision to invest in the Pakistan Stock Exchange (PSX).Design/methodology/approachExisting behavioral finance theories serve as a foundation for hypotheses. Further hypotheses were investigated by disseminating questionnaire results from a number of individual Pakistani investors. Brokerage and asset management fund managers were also questioned in semi-structured interviews. The obtained data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
2
0
0
Order By: Relevance
“…Overconfidence bias can occur in novice investors or young investors because they prefer risk and they immediately want to make investment decisions quickly without going through a process of analysis and gathering enough information. The results of this study are in line with research conducted by , Chishti et al, (2022), and research conducted by Adil et al, (2022) found that overconfidence bias affects investment decisions. Someone who has high overconfidence bias behaviour will be bolder in making investment decisions, while investors who have low overconfidence bias behaviour tend to be more careful in making investment decisions.…”
Section: The Influence Of Overconfidence Bias On Investment Decisionssupporting
confidence: 90%
See 1 more Smart Citation
“…Overconfidence bias can occur in novice investors or young investors because they prefer risk and they immediately want to make investment decisions quickly without going through a process of analysis and gathering enough information. The results of this study are in line with research conducted by , Chishti et al, (2022), and research conducted by Adil et al, (2022) found that overconfidence bias affects investment decisions. Someone who has high overconfidence bias behaviour will be bolder in making investment decisions, while investors who have low overconfidence bias behaviour tend to be more careful in making investment decisions.…”
Section: The Influence Of Overconfidence Bias On Investment Decisionssupporting
confidence: 90%
“…The results of this study are in line with research conducted by Akinkoye & Bankole, (2020), Maqsood et al, (2022), Adil et al, (2022, Gupta & Shrivastava, (2022), and research Chishti et al, (2022) which states that the herding effect behavioural bias affects the investment decision. The influence of the herding effect means that an investor who applies irrational behavioural bias or herding effect will increase their investment decision-making.…”
Section: The Influence Of Herding Effect On Investment Decisionssupporting
confidence: 90%